A Turkish perspective on the ethics of ‘safe zone’: the evolution of the concept in Turkish–American relations from Iraq (1991–2003) to Syria (2012–2016) - ÇETİNOĞLU HARUNOĞLU, AYŞE NUR (Palgrave Macmillan, 2019)
‘Safe zone’ is a transnational concept, including a moral understanding. This article departs from the idea that with the onset of the post-Cold War period, the concept of ‘safe zone’ has been a critical point of fluctuation, whereby Turkey and the USA faced important challenges in their bilateral relations. Accordingly, the article aims to examine the understanding of the concept by Turkey, to question the morality of the concept from Turkish perspective and to discuss its implications for Turkish–American relations. It also intends to analyse to what extent the recent discussions on Syria reveal a continuity with or a change from the discussions on Northern Iraq of 1990s. This study refers to Turkish officials’ statements as well as the debates held in Turkish Grand National Assembly, to reveal the evolving perceptions and/or interpretations of ‘safe zone’ by Turkish authorities. © 2019, The Editor of the Journal.
Keywords: Iraq; Safe zone; Syria; Turkish–American relations